Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1155/2020/8319570
|View full text |Cite
|
Sign up to set email alerts
|

Early versus Delayed Phacoemulsification and Intraocular Lens Implantation for Acute Primary Angle-Closure

Abstract: Purpose. To compare the effects of early phacoemulsification and intraocular lens implantation (phaco/IOL), delayed phaco/IOL after initial laser peripheral iridotomy (LPI), and conventional LPI alone in patients with acute primary angle-closure (PAC). Methods. Patients with acute PAC were included in the study, and those with secondary glaucoma, prior ocular trauma, or other ocular diseases and those who had undergone ocular surgeries previously were excluded. Patients were categorized into three groups: Grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Most previous studies are merely focused on the visual prognosis of lensectomy. Since the treatment option, the sample size, the follow-up period, the study design, and the outcome measures are individually different among these previous and current studies, we cannot directly compare the treatment outcomes of APAC, but visual outcomes in the present study were slightly better than, and the IOP and the ECD were almost equivalent to, those in previous studies, as shown in Table 3 [ 2 , 4 , 5 , 8 – 10 , 15 ] Lam et al demonstrated that lensectomy was superior to LI in terms of reducing the IOP rise [ 1 ] Aung T et al showed that the majority of eyes developing IOP rise after LI for APAC occurred within 6 months from the onset [ 16 ].…”
Section: Discussionmentioning
confidence: 65%
“…Most previous studies are merely focused on the visual prognosis of lensectomy. Since the treatment option, the sample size, the follow-up period, the study design, and the outcome measures are individually different among these previous and current studies, we cannot directly compare the treatment outcomes of APAC, but visual outcomes in the present study were slightly better than, and the IOP and the ECD were almost equivalent to, those in previous studies, as shown in Table 3 [ 2 , 4 , 5 , 8 – 10 , 15 ] Lam et al demonstrated that lensectomy was superior to LI in terms of reducing the IOP rise [ 1 ] Aung T et al showed that the majority of eyes developing IOP rise after LI for APAC occurred within 6 months from the onset [ 16 ].…”
Section: Discussionmentioning
confidence: 65%
“…18,29 A recent study encouraged phacoemulsification after AACG to enhance VA and control IOP, although the cataract operation was risky. 4,30…”
Section: Discussionmentioning
confidence: 99%
“…It is known that LE in PACG, compared with combined lensectomy and trabeculectomy, is more effective in terms of the ACA opening and allows maintaining the result for at least 6 months after the treatment 55. There are many studies devoted to the advantages of LE over LPI in acute primary closed angle 56,57. The insufficiency of LPI for the treatment of acute primary closed angle is proven by the fact that 30% of patients subsequently require trabeculectomy due to IOP decompensation 58.…”
Section: Discussionmentioning
confidence: 99%